Pemberdayaan petani perempuan dalam membangun pengelolaan pertanian berkelanjutan: Studi kasus usaha pertanian organik di Desa Claket, Jawa Timur - Vanda Ningrum; Deshinta Vibriyanti; Sari Seftiani (Research Centre for Population, National Research and Innovation Agency (BRIN), 2021)
Women farmers’ vulnerability due to low access to resources, reduced soil fertility, and the inability of farmers to obtain added value in the market causes poverty upwards among women farmers. Empowerment is an essential concern to improve their quality of life. This study aims to analyse the process of empowering women in organic farming models and the Participatory Guarantee System for organic standards. The study was conducted by taking the case of women farmers community in Claket Village, Mojokerto Regency, East Java Province. The qualitative research approach with data collection techniques through interviews with 16 informants. The results showed that the farmer empowerment was carried out in two processes. Firstly, by changing conventional agricultural cultivation behavior into organic cultivation. Secondly, by establishing a Participatory Guarantee System for organic that can increase the autonomy of women farmers both in terms of cultivation and involvement in the agricultural chain system. Both empowerment processes can be carried out for women farmers despite they have low educational background, limited land, multiple roles in the household, or in older ages. In addition, patience, the nature of togetherness, and the desire to learn are the keys to the success of organic farming businesses in women farmers group.